Phenomenon responses of two kiwifruit genotypes to calcareous and iron treatment in pot experiments - Amparo Primo-Capella; Laura Catalá-Senent; M. Ángeles Forner-Giner; M. Rus Martínez-Cuenca (Horticulture, Environment, and Biotechnology, 2026)
Screening Fe deficiency-tolerant genotypes is an environment-friendly and long-term effective strategy to cope with bicarbonate chlorosis stress in kiwifruit. We investigated the physiological response of two Actinidia chinensis var. deliciosa genotypes, cv. ‘Hayward’ and cv. ‘Tomuri’, when grown in the control solution (20 µM FeEDDHA, Ct) and two iron-deprived conditions: (1) no Fe (0 µM FeEDDHA, -Fe) and (2) induction of Fe deficiency by adding10 mM HCO 3 (Bic). After 45 treatment days, the -Fe and Bic plants exhibited leaf chlorosis symptomatology, as detailed by all the parameters, especially under the Bic conditions. The photosynthesis rate and the Fv/Fm time-course measurements reflected damage to leaf photosystems from early time points, especially in Hayward. The strategy I responses (reduction and acidification capacities) generally reduced, especially by the Bic treatment in both genotypes. However, Tomuri presented a more optimized system for mobilizing root Fe and maintaining photosynthetic activity with the Bic treatment by keeping proton and the Ferric Chelate Reductase levels better than Hayward. The most marked drop was for Chl in the Tomuri -Fe results from no Fe and biomass reduction, while the more attenuated decrease in Hayward depended only on ion nutrition. The results contribute by identifying potential responses in kiwifruit for Fe deprivation tolerance in calcareous soils.

Packaging colour and consumer expectations: Insights from specialty coffee - Fabiana M. Carvalho; Renata A.S. Forner; Eric B. Ferreira; Jorge H. Behrens (Food Research International, 2025)

Ecological restoration of field margins enhances biodiversity and multiple ecosystem services in rice agroecosystems - N. Pérez-Méndez; C. Alcaraz; M. Catala-Forner (Agriculture, Ecosystems & Environment, 2025)

Enhanced diversity of aquatic macroinvertebrate predators and biological pest control but reduced crop establishment in organic rice farming - N. Pérez-Méndez; M. Martínez-Eixarch; R. Llevat; D. Mateu; H.J. Marrero; N. Cid; M. Catala-Forner (Agriculture, Ecosystems & Environment, 2023)

LACTB induces cancer cell death through the activation of the intrinsic caspase-independent pathway in breast cancer - Juan M. Gonzalez-Morena; Sara Escudeiro-Lopes; Jessica Mariane Ferreira-Mendes; Pavel Jakoube; Valentina Cutano; Judith Vinaixa-Forner; Petra Kralova Viziova; Andrea Hartmanova; Radislav Sedlacek; Susana Machado; Beata Malcekova; Zuzana Keckesova (Apoptosis, 2023)
Background LACTB was recently identified as a mitochondrial tumour suppressor that negatively affects cancer cell proliferation by inducing cell death and/or differentiation, depending on the cell type and tissue. However, the detailed mechanism underlying the LACTB-induced cancer cell death is largely unknown. Methods We used cell-based, either in 2D or 3D conditions, and in vivo experiments to understand the LACTB mechanisms. In this regard, protein array followed by an enrichment analysis, cell proliferation assays using different compounds, western blot analysis, flow cytometry and immunofluorescence were performed. Differences between quantitative variables following normal distribution were valuated using Student t test for paired or no-paired samples according to the experiment. For in vivo experiments differences in tumour growth were analyzed by 2-way ANOVA. Results We show, that LACTB expression leads to cell cycle arrest in G1 phase and increase of DNA oxidation that leads to activation of intrinsic caspase-independent cell death pathway. This is achieved by an increase of mitochondrial reactive oxygen species since early time points of LACTB induction. Conclusion Our work provides a deeper mechanistic insight into LACTB-mediated cancer-cell death and shows the dynamics of the cellular responses a particular tumor suppressive stimulus might evoke under different genetic landscapes.

The main drivers of methane emissions differ in the growing and flooded fallow seasons in Mediterranean rice fields - Maite Martínez-Eixarch; Carles Alcaraz; Marc Viñas; Joan Noguerol; Xavier Aranda; Frances-Xavier Prenafeta-Boldú; Mar Català-Forner; M. Siobhan Fennessy; Carles Ibáñez (Plant and Soil, 2021)
Purpose To assess 1) the cumulative greenhouse gas emissions –GHG- and global warming potential (methane – CH 4 - and nitrous oxide) from rice fields in the growing and fallow seasons, and 2) the environmental and agronomic drivers of CH 4 emissions, and their relative capacity to explain CH 4 variation. Methods A two-year multisite field experiment covering the agronomic and environmental variability of a rice growing area in NE Iberian Peninsula was conducted with monthly samplings of GHG and monitoring of both environmental and agronomic factors. Information-theoretic framework analysis was used to assess the relative contribution of the environmental and agronomic variables on methane emissions. Results Two thirds of the CH 4 is emitted in the fallow season. Edaphic factors exert more influence during the growing season whereas agronomic factors have a higher impact in the fallow. The implications of these findings on the design of improved mitigation options rice are discussed. Conclusions Soils with higher soil sulphate concentration, bulk density and clay content emit less CH 4 in growing season. In the fallow season, the rates of both straw input and nitrogen fertilization stimulate CH 4 emissions. Graphical abstract

Effects of high levels of zinc and manganese ions on Strategy I responses to iron deficiency in citrus - Mary-Rus Martínez-Cuenca; Ana Quiñones; Domingo J. Iglesias; M. Ángeles Forner-Giner; Eduardo Primo-Millo; Francisco Legaz (Plant and Soil, 2013)

The effect of sodium bicarbonate on plant performance and iron acquisition system of FA-5 (Forner-Alcaide 5) citrus seedlings - Mary-Rus Martínez-Cuenca; Domingo J. Iglesias; M. Angeles Forner-Giner; Eduardo Primo-Millo; Francisco Legaz (Acta Physiologiae Plantarum, 2013)

Relationship between hydraulic conductance and citrus dwarfing by the Flying Dragon rootstock (Poncirus trifoliata L. Raft var. monstruosa) - B. Martínez-Alcántara; J. Rodriguez-Gamir; M. R. Martínez-Cuenca; D. J. Iglesias; E. Primo-Millo; M. A. Forner-Giner (Trees, 2013)

Fate of 15N-Labeled Potassium Nitrate in Different Citrus-Cultivated Soils: Influence of Spring and Summer Application - Ana Quiñones; Belén Martínez-Alcántara; J. Miguel Martínez; M. Ángeles Forner-Giner; Domingo J. Iglesias; Eduardo Primo-Millo; Francisco Legaz (Water, Air, & Soil Pollution, 2012)

Water-deficit tolerance in citrus is mediated by the down regulation of PIP gene expression in the roots - Juan Rodríguez-Gamir; Gema Ancillo; Frederic Aparicio; Mireia Bordas; Eduardo Primo-Millo; M. Ángeles Forner-Giner (Plant and Soil, 2011)

Hydraulic and Chemical Responses of Citrus Seedlings to Drought and Osmotic Stress - M. Ángeles Forner-Giner; Juan Rodríguez-Gamir; Eduardo Primo-Millo; Domingo J. Iglesias (Journal of Plant Growth Regulation, 2011)

Mechanical model of the recovery from stumbling - A. Forner Cordero; H. J. F. M. Koopman; F. C. T. van der Helm (Biological Cybernetics, 2004)

Effect on Resistance to Tylenchulus semipenetrans of Hybrid Citrus Rootstocks Subjected to Continuous Exposure to High Population Densities of the Nematode - S. Verdejo-Lucas; M. Galeano; F.J. Sorribas; J.B. Forner; A. Alcaide (European Journal of Plant Pathology, 2003)

Role of peripheral afference during acquisition of a complex coordination task - R. G. Carson; C. J. Smethurst; M. Forner; D. P. Meichenbaum; D. C. Mackey (Experimental Brain Research, 2002)

Genetic analysis of apomixis in Citrus and Poncirus by molecular markers - R. García; M. J. Asíns; J. Forner; E. A. Carbonell (Theoretical and Applied Genetics, 1999)